How Do We Explore the Fifth Dimension: Spirituality? - Mark Goodman
Spirituality has been a core component of human existence from the very beginning of human life. From mysticism to healing to psychics, millions of people throughout history have explored their spiritual connections to something greater than themselves. We explore the nature of spirituality and why it is so hard for humans to understand its dimensions.